Dentin primer based on a highly functionalized gelatin-methacryloyl hydrogel. Issue 2 (February 2023) - Alia, Ala; Gao, Feng; Mitchell, John C.; Gasiorowski, Joshua; Ciancio, Mae; Kuppast, Bhimanna; Pfeifer, Carmem; Carrilho, Marcela R.
Abstract: Gelatin-methacryloyl hydrogels (GelMA) have demonstrated their utility as scaffolds in a variety of tissue engineering applications. Objectives: In this study, a highly functionalized GelMA hydrogel was synthesized and assessed for degree of functionalization. As the proposed GelMA hydrogel was coupled to a visible-light photoinitiator, we hypothesized it might serve as base to formulate a model dentin primer for application in restorative dentistry. Methods: GelMA was mixed with photoinitiator lithium phenyl-2, 4, 6-trimethylbenzoylphosphinate (LAP), photopolymerized for 0–40 s using a dental light-curing device and tested for extrudability, degree of photo-crosslinking (DPxlink ), water sorption/solubility/swelling (WS/SL/SW) and apparent modulus of elasticity (AE). Model dentin primer was prepared by mixing GelMA+LAP with a primer of a commercial three-step etch-and-rinse adhesive. After application of GelMA-based primer to acid-etched dentin, samples were bonded with correspondent adhesive agent, photopolymerized and had their immediate bond strength compared to control samples primed and bonded with the same commercial material. Results: Extrudability of hydrogel was confirmed using a microsyringe to write the acronym "CDMI". DPxlink of GelMA+LAP changed significantly as a function of photopolymerization time (20 s < 30 s ≤ 40 s). WS, SL and SW were significantly reduced in hydrogels polymerized for 30 and 40 s. AE of hydrogels varied significantly as a function of photopolymerization time (20 s < 30 s ≤ 40 s; 20 s ‡ 40 s). Bond strength of dentin primed with GelMA-based primer was lower (∼29.3 MPa) but not significantly of that of control (∼34.6 MPa). Conclusions: Optimization of a GelMA-based dentin primers can lead to the development of promising biomimetic adhesives for dentin rehabilitation.